The role of marketing recovery in improving the organization's reputation An applied study of a sample of private bank managers in Baghdad - Ali Ramadhan, Hatem; Hammoud Jathir, Prof. Saadoun (Journal of Economics and Administrative Sciences, 2020)
This research aims to know and the role of the marketing recovery dimensions in improving the organization's reputation through an exploratory study of private banks in the city of Baghdad. The aim of the research is to define the role of the marketing recovery through its dimensions (compensation, apology, speed of response, assistance and problem solving), in improving the organization's reputation, as the research will attempt to provide a theoretical framework for the dimensions studied through the most important of what researchers presented and then conduct the applied aspect of the research. Data were collected using a questionnaire-based survey consisting of 35 questions and distributed to 110 managers of private banks in the city of Baghdad. Therefore, the research attempts to answer a set of questions that embody the research problem (is there a role to exclude the marketing recovery on the dimensions of the organization's reputation), and in order to analyze the data obtained from the questionnaire, statistical methods such as the arithmetic mean, standard deviation, coefficient of variation, and the simple correlation coefficient were used, The results showed that there is an effect of the marketing recovery dimensions on improving the organization's reputation. Therefore, the research recommends that the bank's administration should work to improve the bank's reputation by focusing on and increasing attention to the dimensions of recovery in banks to obtain customer satisfaction. The researcher has faced the difficulty of obtaining data and the unwillingness of banks to cooperate with him, so it is not possible to generalize the results of the research to the research community for the privacy of banks compared to other service institutions. The research banks should use the marketing recovery dimensions to contribute to achieving customer satisfaction. Therefore, the research will contribute to knowing the mechanisms that help the bank to recover, improve its reputation and increase customer satisfaction.